Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Perhiasan Imitasi Pada Toko Rara Aksesoris - Yasmita, Hafsyah; Nasution, Juliana; Dharma, Budi (Oikonomia: Jurnal Manajemen, 2024)
The purpose of this study is to identify and evaluate how price and product quality influence customers' decision to buy costume jewelry from Rara Aksessories. Quantitative research methodology. A total of 100 Rara Aksessories customer respondents from the entire population who made more than 2 transactions online participated in this study using associative techniques.  Information was collected through a questionnaire given to respondents and analyzed using multiple linear regression analysis methods in the IBM SPSS Statistic 27 program. The research findings show that price and quality simultaneously have a positive influence on imitation jewelry purchasing decisions at Rara Accessories. Suggestions Future researchers are expected to add other variables and other research stores/locations.